Reduced levels of mitochondrial ribosomal protein MRPL54 does not alter Apc related adenoma formation - Claudia N. Spaan; Eileen Daniels; Wouter L. Smit; Ruben J. de Boer; Joana Silva; Jacqueline L. M. Vermeulen; S. Meisner; Vanesa Muncan; Riekelt H. Houtkooper; Jarom Heijmans (PLoS ONE, 2026)
Reprogramming of energy metabolism is one of the hallmarks of cancer cells and mutations that modify wild type intestinal cells to colon carcinomas increases cellular energy expenditure. Mitochondria are the main site for ATP production in (cancer) cells and disrupting their function results in impaired tumor forming efficacy. The mitochondrial ribosomal proteins (MRPs) constitute the ribosome specifically in mitochondria, and as such are crucial for the translation process of the electron transport chain complex subunits. We hence aimed to explore the consequence of reduced MRP expression on adenomagensis and investigate this in a genetic mouse model with bodywide heterozygosity for Mrpl54 . We show that Mrpl54 heterozygosity does not alter adenoma formation, intestinal proliferation or apoptosis in a heterozygous Apc model. Furthermore, diminished Mrpl54 expression did not decrease stemness or global parameters of metabolism in colorectal cancer cell lines.